Development and Validation of a Bedside Scale for Assessing Upper Limb Function Following Stroke: A Methodological Study. [version 1; peer review: 2 approved] - Sampath Kumar Amaravadi; Vijayakumar Palaniswamy; Akshatha Nayak; Dhaval Pawani; Prasanna Mithra; Ashish John Prabhakar; Abraham M. Joshua (F1000Research)
Background Numerous tools are available for evaluation of upper limb (UL) functions among stroke survivors. Despite the excellent psychometric properties, many require considerable amount of time, are resource-intensive, and often impractical for bedside evaluation. Objectives To develop and concurrently validate a simple, resource-efficient, and time-efficient bedside tool for evaluating UL function in stroke survivors. Methods Relevant literature review was carried out to conceptualize and define the theoretical framework of day-to-day UL movement tasks. Subsequently, an item pool of 18 UL movements was developed. A mini-Delphi method was employed to verify content validity. During the iterative rounds, 18-items were revised and refined to a 12-items scale. The final bedside upper limb evaluation tool (BUFET) scale underwent concurrent validation by correlating the scores with Wolf Motor Function Test (WMFT) scores using Spearman’s correlation coefficient. Internal consistency was evaluated through Cronbach’s alpha. Results Concurrent validity and internal consistency of the scale were supported by a high correlation coefficient (r = 0.937; p<0.001) with WMFT and high Cronbach’s alpha (0.948). Conclusions Newly developed BUFET was found to be a valid and reliable bedside tool in the evaluation of upper limb functions and can be administered in a resource and time-efficient manner.